Pesky trachoma suspect finally caught. Issue 6 (17th May 2004) - Miller, K; Pakpour, N; Yi, E; Melese, M; Alemayehu, W; Bird, M; Schmidt, G; Cevallos, V; Olinger, L; Chidambaram, J; Gaynor, B; Whitcher, J; et al.
Abstract : Aim: Face seeking flies have long been thought to transmit Chlamydia trachomatis, the causative agent of trachoma, but this has never been proven. The four criteria proposed by Barnett, previously used to incriminate other arthropods suspected of transmitting disease, were examined. One of these criteria remains unmet: the repeated demonstration of the presence of C trachomatis on flies. The authors used polymerase chain reaction (PCR) to look for the presence of C trachomatis DNA on flies in the Gurage Zone of Ethiopia. Methods: Using sticky paper, one fly was collected from the face of each of 103 children aged 1–10 years. The piece of fly paper to which the fly was attached was cut out, followed by the collection of an empty piece from an arbitrary area of the fly paper, which served as control. Roche Amplicor PCR kits were used to detect C trachomatis DNA. Results: Evidence of C trachomatis by PCR was found on 15 of 103 flies versus 0 of 103 controls (p = 0.0001). Conclusion: These results meet the final criterion needed to incriminate flies as a vector of trachoma. However, interventional studies will be needed to show the importance of fly control.